PENGARUH STRATEGI PEMASARAN TERHADAP VOLUME PENJUALAN PADA PT. NARINDO SOLUSI TELEKOMUNIKASI TAP MANDREHE KABUPATEN NIAS BARAT - Pilipus Gulo; Serniati Zebua; Yupiter Mendrofa; Eliagus Telaumbanua (Lembaga Pengembangan Kinerja Dosen, 2026)
The sale of the starter pack of PT. Narindo Tap Mandrehe Telecommunication Solutions experienced a significant and fluctuating decline from April to December 2024, although it had increased at the beginning of the year. This indicates problems in the company's marketing strategy, such as unstable network/signals, less competitive prices, and slow marketing services in responding to customer complaints. This study aims to find out whether there is an influence of Telkomsel's marketing strategy on sales volume at PT. Narindo Telecommunication Solutions Tap Mandrehe West Nias Regency and how much influence it has. The method used by the researchers is qualitative, with the technique of a linear regression of the simplest line. The data collection technique used in this study was the distribution of questionnaires to respondents. In this study, which is a validity and reliability test, correlation coefficient test, classical assumption test with two tests used, namely normality test and linearity test, simple linear regression test, determination coefficient test and T test. This research was conducted at PT. Narindo which is located in Fadoro Village, Mandrehe District, West Nias Regency. The research results showed that the results for the hypothesis test results obtained by a calculation of 8,263 with a significant value of 0.000. Dimalnal baltals mean 0.05 with a tally of 6,789 that shows the value of > talbel (6,789>2,034) that is alrtinyal Something is accepted and Ho is accepted. So that the dalpalt was concluded balhwal aldal the influence of the straltegi pemalsalraln the volume of the sellers of PT. Narindo. The data for the test of the R Squalre (R2) determination coefficient was obtained before 0.583 i.e. then it was mammalized to the formula KD r2 x 100% altalu KD = 0.583 x 100% = 58.3%. So that the influence of the distribution distribution of the distribution is 58.3% compared to the remaining 41.7% influenced by the valrialbel circulation of the distribution of the same research.